Student Research Trends in the History of Islamic Civilization at UIN Sunan Ampel Surabaya - Hajar, Imam Ibnu; Juma', Juma' (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to systematically describe trends or tendencies in student research or thesis as a final assignment as a condition for obtaining a bachelor's degree. The research approach is in the form of library research with a qualitative descriptive method. This research focuses on student thesis from 2020-2022, a total of 191 student thesis. This study found that there were certain trends in student research, in the form of research topics/themes and types of research. It is hoped that the results of the research will become a benchmark for office holders and students to broaden the field of historical studies, either by theme or by type of research.